Production Area (Concessions) Role on Landscape Environment Management in South Sumatra - Edwin Hermawan; Moh. Rasyid Ridho; Muhammad Yazid (Sriwijaya Journal of Environment, 2020)
Gap existing in the landscape are partial practices on environment management and social programs from each of landscape stakeholders which cause cumulative duplication or incontinuity between programs. The objective of this research is to analyze production area role in the landscape environment management in South Sumatra particularly Musi Banyuasin and Banyuasin Districts. Using survey method and purposive sampling, 8 companies representatives are interviewed regarding current environment management system and the relation with external factors with landscape approach overview. The results: (1) Land-use planning should be in place prior the development of concession permit and concessions as implementer of provincial and national agendas on local investments; (2) Concession monitoring efforts could give input on the conformity towards the law enforcement in environment management which should be expressed through the year.; (3) Concessions ideally have the role as connector to community and protected areas, connecting to government programs, raising awareness as well as providing assistance in economic empowerment to the community, reducing dependency towards forests; (4) The report from wildlife and its habitat monitoring (buffer area) surrounding concession should also be shared with Environmental Agency (DLH), Forest Management Unit (KPH), National Park and Natural Resource Conservation Center (BKSDA) for potential or existing wildife corridors or ecosystem essentials area; (5) Concession could collaborate with conservation area as well as other governmental programs to maximize the impact and efficiency of the programs. Together with community and protected areas, concessions have significant area size and have the capacity and resources to also take part in the landscape management. Joint monitoring and programs would be tremendous achievement for the landscape approach.